Pessoa’s Archive: a study about understandings and representations of archival manuscripts in the Casa Fernando Pessoa - Aldabalde, Taiguara Villela (Anais do Museu Paulista: História e Cultura Material, 2018)
This article presents the results of a postdoctoral investigation. The research aims to discuss the understanding of the archival manuscripts of Fernando Pessoa as a spoil and to infer the quantitative representation of these documents, as well as to identify the practices through which these representations have been mediated in the Casa Fernando Pessoa. The documentary-historical method is adopted considering the products, the museum space, and the administrative documentation from 2006 to 2017 as the empirical basis. The following are the consequences of understanding the archive as a spoil: a mix of archives as a result of improper additions, a lack of control over the preservation of the documents’ authenticity, absence of archival representations and archival bonds, the thematization of the archive in detriment of the archival description, the disarticulation between private collections and public archives and the no-compliance of methodological standards compatible with a closed archival fond. The Casa Fernando Pessoa is a place of convergence between museums’, archives’, and libraries’ materials. The total quantitative result of the representations of the archival manuscripts of Fernando Pessoa (1888-1935) is 225 representations. The following categories of representation have been identified: fac-similar, artistic, visual, graphic, and digital. This research identified the occurrence of 22 practices distributed in these following types: historical recreation, exhibition, multimedia exhibition, course, ephemerides, webcast, and digital curation. It was possible to establish that Casa Fernando Pessoa contributes to the democratization of the manuscripts’ representations through practices of diffusion and cultural mediation with archival material.